BRCA 1/2-Mutation Related and Sporadic Breast and Ovarian Cancers: More Alike than Different - Burgess, Melissa A.; Puhalla, Shannon L. (Frontiers in Oncology, 2014)
No longer is histology solely predictive of cancer treatment and outcome. There is an increasing influence of tumor genomic characteristics on therapeutic options. Both breast and ovarian cancers are at higher risk of development in patients with BRCA 1/2-germline mutations. Recent data from the Cancer Genome Atlas (TCGA) and others have shown a number of genomic similarities between triple negative breast cancers and ovarian cancers. Recently, poly (ADP-ribose) polymerase (PARP) inhibitors have shown promising activity in hereditary BRCA 1/2-mutated and sporadic breast and ovarian cancers. In this review, we will summarize the current literature regarding the genomic and phenotypic similarities between BRCA 1/2-mutation related cancers, sporadic triple negative breast cancers, and sporadic ovarian cancers. We will also review phase I, II, and III data using PARP inhibitors for these malignancies and compare and contrast the results with respect to histology.